2018
DOI: 10.3389/fneur.2017.00713
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Anterior Circulation Large Vessel Occlusion in the Elderly

Abstract: Endovascular treatment of anterior circulation large vessel occlusion in the elderly population presents special challenges and opportunities. In this review, we discuss the published literature regarding thrombectomy in elderly patients and also discuss specific issues related to treatment in this patient population. In summary, while the overall outcomes following thrombectomy in elderly patients are worse than following thrombectomy in younger patients, there appears to be a similar benefit as in young pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Our findings showing poor outcomes after ET are consistent with prior single arm studies, as previously reviewed by Jayaraman et al 20 and as reported in an earlier meta-analysis 21. Some studies attributed worse outcomes in the elderly to potential higher comorbidities, procedural variables, and impaired collaterals 20–22.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings showing poor outcomes after ET are consistent with prior single arm studies, as previously reviewed by Jayaraman et al 20 and as reported in an earlier meta-analysis 21. Some studies attributed worse outcomes in the elderly to potential higher comorbidities, procedural variables, and impaired collaterals 20–22.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrate that an age of ≥72 years is a negative predictor of poor outcome in patients with anterior circulation occlusion but does not independently predict an increased rate of functional dependence in the posterior circulation group. Our findings and those of previous studies have consistently shown that age is an independent predictor of functional independence and mortality after thrombectomy in elderly patients with acute anterior circulation stroke [ 14 , 15 ]. Although the BASICS study demonstrated that mechanical thrombectomy is safe for acute circulation stroke, its effectiveness has not yet been confirmed [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…The verification of the internal validation group (training group) by bootstrap analysis further confirmed the reliability of the present nomogram. Although several studies have examined the relationship between risk predictors and stroke outcome after mechanical thrombectomy [ 14 , 15 , 20 ], there is growing evidence that nomograms have a better performance than risk predictors [ 10 , 11 ]. In contrast to the risk group, a nomogram model provides a visualized and individualized estimate of the prediction probability of a specific outcome for an individual patient, as well as an important tool of medical decision-making based on the individual's disease characteristics.…”
Section: Discussionmentioning
confidence: 99%
“… 6 In addition, this patient population became disabled after stroke more often than the younger population. 7 Elderly patients will soon represent the majority of BAO victims, resulting in a substantial impact on health services in the near future. 8 While interventional therapy for elderly patients with acute BAO was currently not considered the standard of care, it was offered at many comprehensive stroke centers or tertiary hospitals in China.…”
Section: Introductionmentioning
confidence: 99%